Investigating school conditions for teachers' professional learning and development in Indonesia. Issue 2 (15th March 2022) - Rahman, Abdul
ABSTRACT: Schools are expected to provide favourable conditions for teachers' professional learning and development (PLD). Situated perspectives suggest that personal, professional and systemic conditions are influential for teacher PLD. Yet, supportive conditions for teachers' PLD are limited for the majority of schools in regional Indonesia. Drawing on semi-structured interviews with teachers from three regional schools in Sulawesi Selatan, Indonesia, this article uncovers situated patterns of practices that shape school conditions for teachers' PLD. Teacher participants indicated school norms, resources and facilities, school status and history, and students and principal leadership as influential for their PLD. Professional communication and interactions among teachers along with leadership by principals lay the foundation for favourable school conditions for PLD.